[18F]FDG PET/CT to reduce the need for sentinel lymph node biopsy in early-stage oral cancer: PETN0-study protocol - Roosmarijn S. Tellman; Dominique N.V. Donders; Anne I. J. Arens; Koos Boeve; Adrienne H. Brouwers; Simone E.J. Eerenstein; Sylvia L. van Egmond; Thomas J.W. Klein Nulent; W. Martin C. Klop; Martin Lacko; Jochem A.J. van der Pol; Daphne D.D. Rietbergen; et al. (PLoS ONE, 2025)
Using reliable techniques for detecting lymph node metastases (LNM) in oral squamous cell carcinoma (OSCC) is crucial for adequate neck treatment. Currently, palpation of the neck, computed tomography, magnetic resonance imaging, ultrasound-guided fine needle aspiration cytology and/or sentinel lymph node biopsy (SLNB) are used to stage the neck in early-stage OSCC. SLNB is a reliable diagnostic technique to detect occult LNM. However, management of the neck with SLNB has its limitations. First of all, SLNB is an invasive procedure with associated morbidity and approximately 20–30% of patients require a subsequent neck dissection. Moreover, performing a subsequent neck dissection is more complex than elective neck dissection, and carries a higher risk of complications. Therefore, it is important to improve patient selection for SLNB. Fluor-18-fluorodeoxyglucose ([18F]FDG) positron emission tomography/computed tomography (PET/CT) has shown promising results for LNM detection. The aim of the PETN0 study, a prospective Dutch multicenter cohort study (registration number NL83442.041.22), is to reduce the need for SLNB by developing scoring criteria for [18F]FDG PET/CT with a high positive predictive value (PPV) in patients with early-stage OSCC. Developing scoring criteria for a high PPV can reduce SLNBs and second-stage neck dissections by performing a neck dissection together with resection of the primary tumor in patients with predicted LNM. When focused on high PPV the sensitivity will probably be lower, but missed LNM will be detected by SLNB when performed after negative [18F]FDG PET/CT. Patients (n = 159) with cT1-3N0 OSCC (8th TNM edition; only when T3 is assessed based on tumor dimensions of >2 and ≤4 cm, with DOI > 10 mm), candidate for transoral excision and SLNB, are included in the study. [18F]FDG PET/CT will be conducted within a maximum of three weeks before SLNB. A cost-effectiveness analysis will also be performed, together with quality of life assessment using questionnaires.